Acute intracranial hemorrhage in 76 COVID-19 patients during the first and second pandemic waves - Georgievski-Brkić Biljana; Vukićević Marjana; Debeljković Vladimir; Nikčević Ljubica; Stanisavljević Nataša; Kostić Dejan; Vitošević Filip; Jovanović Verica; Marinković Slobodan (Vojnosanitetski Pregled)
Background/Aim. There is limited data on the frequency of intracranial hemorrhage (ICrH) in the first wave [beta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)] and second wave (delta variant of SARS-CoV-2) coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to analyze the appearance of ICrH in COVID-19 patients (CP). Methods. Among 505 CP treated at the Special Hospital for Cerebrovascular Diseases “Sveti Sava” intermittently during the 2020–2021 period, ICrH was diagnosed in 76 (15.1%) patients. The available information from the medical records regarding clinical, demographic, as well as radiological data (multislice computed tomography examination of the endocranium) was collected and analyzed. Results. In the first wave, out of 308 CP, 63 (20.5%) were diagnosed with ICrH. In the second wave, out of 1 97 CP, ICrH was diagnosed in 13 (6.6%) patients, which was a statistically significant difference (p < 0.002). There was no statistically significant difference for the presence of hyper-tension (p = 0.271), diabetes mellitus (p = 0.558), and chronic obstructive pulmonary disease (p = 0.794) among CP with ICrH comparing the two waves of the pandemic. However, a statistically significant difference was proven in the frequency of patients with atrial fibrillation and anticoagulant drug therapy (p = 0.021 each). There was no statistically significant difference in the frequency of patients with fever ( p = 0.637), fatigue (p = 0.587), hemiparesis (p = 0.831), respiratory symptoms (p = 0.289), and loss of consciousness (p = 0.247). D-dimer values in the second pandemic wave were statistically significantly lower (p = 0.003). The combination of ischemic stroke and ICrH was six times more common in the second wave (p = 0.003). However, cerebral parenchymal hemorrhage was two times less frequent (p = 0.001) in the second wave but with statistically higher frequencies of multifocal (23.1%) and diffuse type (36.4%) of ICrH (p = 0.007). Combined hemorrhages, as well as subarachnoid and subdural sub-types, were more common in the second wave (23.1% each). Fatal outcomes occurred in 38.1% of patients in the first wave compared to 69.2% in the second wave (p = 0.039). Conclusion. In the first pandemic wave of COVID-19, ICrH in CP was significantly more frequent and D-dimer was singled out in laboratory analyses, the values of which were statistically significantly higher in comparison with second wave. In the second wave of COVID-19, parenchymal ICrH was less frequent and multifocal and diffuse ICrH were more common in CP with ICrH. The mortality rate was very high in the second wave.